Proximal row carpectomy - Semprimožnik, Katja (Surgery and surgical endoscopy, 2019)
Background. Proximal row carpectomy is a salvage procedure for arthritic wrists. According to the published literature, the operation preserves mobility and diminishes pain. We compare the outcomes of patients who were operated on at our department to postoperative outcomes published in the literature. Methods. A retrospective review of patients undergoing proximal row carpectomy in our hospital in the last 3 years was performed. All the patients were invited for a follow-up. At the follow-up visit, the movement and strength of both wrists were measured. The patients also completed a short questionnaire. Pre- and postoperative measurements on the operated and un-operated wrist were compared. A literature search regarding proximal row carpectomy was performed. Results. Mobility of the operated wrist before and after operation, grip strength before and after operation, mobility of the operated and unoperated wrist, and grip strength of the operated and unoperated hand were compared. After the surgery, dorsal flexion, volar flexion, ulnar deviation, radial deviation, and active range of motion were 128%, 90%, 97%, 88%, and 97% of the preoperative value, respectively. On average, spherical grip strength was 71% of the preoperative measurements, and cylindrical grip strength was 83% of the preoperative value. Patients achieved 77% of the preoperative grip strength and 66% preoperative finger strength. For the patients whose non-dominant hand was operated on, dorsal flexion and volar flexion were 75% and 66% of the unoperated hand, respectively. Patients whose dominant hand was operated on had dorsal flexion, volar flexion, and ulnar and radial deviation of 57%, 58%, 66%, and 46% of the contralateral side, respectively. On average, power grip and finger strength were 56% and 80% of the unoperated hand, respectively. Conclusion. Proximal row carpectomy successfully diminishes pain and preserves mobility in patients with partial wrist arthrosis. Postoperative results in our hospital are comparable to MINAMed d.o.o. | Leskoškova cesta 10, 1000 Ljubljana those at other medical centers.
Keywords: artroza; kirurško zdravljenje; zapestje